BIOMECHANICS OF FLIGHT PHASE WHEN RUNNING LONG JUMP FROM PLACE OF DIFFERENT QUALIFICATION SPORTSMEN - A. V. Razuvanova; Ye. V. Koshelskaya; V. I. Andreyev; I. V. Kapilevich (Бюллетень сибирской медицины)
Biomechanical features of flight phase when running long jump from place of different qualification sportsmen were investigated by method of Motion Tracking. The obtained results showed that the effective control of body position during the phase of flight can improve the effectiveness of jump actions.. This control is performed by moving parts of the body – bending legs at the knee, extension in the hip joints, the joints of the spine, shoulder joints and, as a consequence, any additional torque, contributing to increase the range of the jumping. In untrained persons the effectiveness of the management body in flight is reduced due to weak coordination and a predominance of actions aimed at safe. All the patterns can be viewed as the result of formation of a particular movement pattern, based on the interaction of vestibular and statokinetic reflexes.